Ethical Theory in Classic German Philosophy Then and Now - Nowak, Ewa; Rockmore, Tom; Scaglia, Lara; Adolphi, Rainer (ETHICS IN PROGRESS, 2021)
The volume brings together contributions in the spirit embodied by Marek J. Siemek († 2011) and Jakub Kloc-Konkołowicz († 2021), two Warsaw philosophers truly devoted to Classical German Philosophy. They were simultaneously in a relationship between thinker and adept, and thinker and thinker. They both taught philosophy, with a strong emphasis on classic German philosophy, at Warsaw University. Under the theme “Ethical Theory in Classic German Philosophy Then and Now,” students and companions continue their discussions with both of them.